Increasing statin prescription rates to prevent cardiovascular disease among high-risk populations: a quality improvement intervention centred on a novel interactive tool. Issue 3 (16th September 2022) - Rashid, Sana; Suero-Abreu, Giselle Alexandra; Tysarowski, Maciej; Um, Hyo-bin; Shah, Kajol; Zhang, Yawen; Douglas, Analise; Matassa, Daniel
Abstract : Statins are indicated for primary and secondary prevention of atherosclerotic cardiovascular disease (ASCVD). Our previous study of 1042 consecutive patient encounters at our large urban academic institution found that one in five patients were not prescribed an appropriate statin therapy. Only one-third of patients had follow-up cholesterol levels ordered to monitor treatment efficacy. In order to improve adherence to cholesterol guidelines at our institution, a quality improvement project was undertaken. We implemented interventions over a 4-month period to improve statin prescription rates: (a) development of an online interactive tool, (b) physician education on updated cholesterol guidelines and utilisation of the tool, (c) display of guideline summary in the workspace and (d) a documentation reminder in the electronic health record. We randomly selected encounter dates, from which 622 consecutive patient encounters were analysed. The primary outcome measures were prescription rates of statins, documentation of a 10-year ASCVD risk score and follow-up cholesterol levels ordered to monitor treatment efficacy. Out of the 622 patient encounters, 232 met statin indication. In this post-intervention group, statin prescription rates improved when compared with the pre-intervention group (90.5% vs 82.3%, p=0.006). Among patients who met statin indication solely via a 10-year ASCVD risk score ≥7.5%, there was an increase in documentation of the calculated 10-year ASCVD risk score (72.3% vs 57.8%; p=0.039) and in statin prescription rate (90.8% vs 67.6%; p<0.001). In addition, there was an increase in follow-up cholesterol levels ordered in all patients included in our study who met statin indication (64.1% vs 33.3%; p<0.001). Our quality improvement project showed higher rates of statin prescription, 10-year ASCVD risk score documentation and treatment monitoring after multiple interventions, centred on an easily accessible online interactive tool.